Transformation of Environmental Education in Pesantren: Integration of Islamic Values and STEAM Approach - Mohamed S.H., Sheik; Sayyi, Ach.; M. Nirmala, M. Nirmala; Elango, S. (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
This study investigates the influence of pesantren, Indonesia's oldest Islamic educational institution, on practicing environmental education based on Islamic values. This study adopts the method of library research, in which it uses secondary data from scientific books, journal articles, research reports, official documents, and Islamic texts. Three main aspects of the analysis include the theological basis of environmental responsibility in the Qur'an, the global and local context of environmental education, and pesantren education in terms of structure and culture. Khalifah, Mizan, and Hifdz al-bah are considered sustainable, ethical frameworks. The findings revealed that pesantren encountered major challenges in combining modern environmental education but possess special strengths like solid moral principles, local values, and close relationships between teachers and students. These include the constraints of the curriculum, the lack of resources, and teachers not being trained for this type of interdisciplinary and STEAM (Science, Technology, Engineering, Arts, Mathematics) methodologies. Notwithstanding these barriers, pesantren can adapt traditional religious teaching to meet contemporary sustainability demands through curriculum reform, community-based initiatives, and partnerships with external funders. The model developed in this study shows that pesantren can be a transformative institution to promote sustainability with a potent amalgamation of Islamic ethical values and modern forms of education. This may lead to a transformative education approach for sustainability from pesantren. The new model underscores systematic curriculum development, teacher capacity-building, and external partners that can help support resource provision. As moral and educational forces in society, pesantren are expected to play important roles in local and global sustainability, shouting to the Sustainable Development Goals (SDGs), especially in quality education and climate action.